2020
DOI: 10.1037/ppm0000215
|View full text |Cite
|
Sign up to set email alerts
|

Natural in the eyes of the (be)holder: A survey on novelty and learning effects in the enjoyment of naturally mapped video game controllers.

Abstract: Video games can be understood as a series of interesting decisions, and the game controllers are key to making those decisions. Advances in gaming technology have encouraged the development of natural user interfaces (NUIs), which should provide a superior user experience as players are able to use preexisting mental models from physical interaction rather than learning an abstract mapping schema. However, anecdotal and previous empirical research suggest the opposite-gamers prefer more familiaralbeit-abstract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Here, we are careful to distinguish perceived naturalness (that a certain controller is seen as more intuitive for a given video game) from more objective measures of naturalness (such as those controllers that progressively embody the natural human senses; Biocca, 1997). For example, Tamborini et al (2010) found that a handheld game controller was perceived as more natural for a bowling video game than an actual bowling ball controller-one explanation being that a video game controller was more familiar to participants (also noted in the study by Liebold et al, 2020). For nostalgic video games, the game and the controller used to play it become perceptually and mentally tied to each other.…”
Section: Nostalgia and Video Gamesmentioning
confidence: 90%
“…Here, we are careful to distinguish perceived naturalness (that a certain controller is seen as more intuitive for a given video game) from more objective measures of naturalness (such as those controllers that progressively embody the natural human senses; Biocca, 1997). For example, Tamborini et al (2010) found that a handheld game controller was perceived as more natural for a bowling video game than an actual bowling ball controller-one explanation being that a video game controller was more familiar to participants (also noted in the study by Liebold et al, 2020). For nostalgic video games, the game and the controller used to play it become perceptually and mentally tied to each other.…”
Section: Nostalgia and Video Gamesmentioning
confidence: 90%
“…Research studies that investigated these new control methods in the 2010s found that these more natural user interfaces (NUIs) tended to produce a heightened sense of presence, greater interactivity, increased realism, and higher levels of enjoyment than traditional gamepad interfaces used to play similar games (Shafer et al, 2011(Shafer et al, , 2014Skalski et al, 2011). However, other evidence suggests that simply having a NUI doesn't always result in a better gaming experience (Bowman et al, 2017;Liebold et al, 2020;Rogers et al, 2015;Seibert & Shafer, 2017). As mentioned, novelty has been forwarded as an explanation for some of the findings of strong impact in the past (Liebold et al, 2020).…”
Section: Interaction Fidelitymentioning
confidence: 99%
“…However, Bowman et al (2017) were quite correct in their assertion that discrete qualities of the differences produced by NUIs versus traditional gamepad controllers are unaccounted for. Some progress has been made on that front, with Bowman and colleagues’ own work leading the way (Bowman et al, 2017; Liebold et al, 2020; Rogers et al, 2015). Others have hinted at the possibility that so-called NUIs may not always be perceived as the most natural control method (Seibert & Shafer, 2017), but those findings were thought to be mostly due to failings of the specific NUI in question.…”
Section: Interaction Fidelitymentioning
confidence: 99%
See 2 more Smart Citations